Where Sex Meets Gender: How Sex and Gender Come Together to Cause Sex Differences in Mental Illness - Christiansen, Dorte M.; McCarthy, Margaret M.; Seeman, Mary V. (Frontiers in Psychiatry, 2022)
Sex differences are prevalent in multiple mental disorders. Internalizing disorders are more commonly diagnosed in women, whereas externalizing and neurodevelopmental disorders are more often diagnosed in men. Significant sex/gender differences are reported in prevalence, symptom profile, age of onset, comorbidities, functional impairment, prognosis, as well as in responses to various treatments. In this conceptual article, we discuss theories and empirical studies of sex- and gender-related influences in mental health, by focusing on three examples: autism spectrum disorder (ASD), acknowledged as a disorder whose roots are mainly biological; eating disorders, whose origins are considered to be mainly psychosocial, and posttraumatic stress disorder (PTSD), an environmentally caused disorder with both psychosocial and biological underpinnings. We examine the ways in which sex differences emerge, from conception through adulthood. We also examine how gender dichotomies in exposures, expectations, role assumptions, and cultural traditions impact the expression of our three selected mental illnesses. We are especially interested in how sex-based influences and gender-based influences interact with one another to affect mental illness. We suggest that sex and gender are multi-faceted and complex phenomena that result in variations, not only between men and women, but also within each sex and gender through alterations in genes, hormone levels, self-perceptions, trauma experiences, and interpersonal relationships. Finally, we propose a conceptual diatheses-stress model, depicting how sex and gender come together to result in multiple sex/gender differences across mental disorders. In our model, we categorize diatheses into several categories: biological, intrapersonal, interpersonal, and environmental. These diatheses interact with exposure to stressors, ranging from relatively minor to traumatic, which allows for the sometimes bidirectional influences of acute and long-term stress responses. Sex and gender are discussed at every level of the model, thereby providing a framework for understanding and predicting sex/gender differences in expression, prevalence and treatment response of mental disorders. We encourage more research into this important field of study.